PENERAPAN BLENDED LEARNING SEBAGAI STRATEGI PENJANGKAUAN PENDIDIKAN PADA PROGRAM KESETARAAN - Elisabeth Lusitania Desiawati; Asep Samsudin; Nunu Mahmud Firdaus (Comm-Edu (Community Education Journal), 2026)
This study examines the application of blended learning as an educational outreach strategy in equivalency programs. The research background is the need for flexible educational access for students with limitations in time, distance, and socioeconomic conditions. The method used is descriptive qualitative through observation, interviews, and documentation with students and tutors in equivalency programs. The results show that blended learning, which combines face-to-face and online learning through digital media such as Zoom, can increase student participation while expanding educational reach. Students can access materials more easily, while tutors can manage learning in a more varied manner. In conclusion, blended learning is effective as an equivalency education outreach strategy, although it requires support from tutors' readiness, technological resources, and student learning motivation.